Dinâmica nutricional em um povoamento híbrido de Eucalyptus urophylla x Eucalyptus globulus em Eldorado do Sul - RS, Brasil - Viera, Márcio (2012)
Understanding of the involved issues in nutritional dynamics process in eucalyptus stands is the base to sustainable management. Objective this study was to determine the nutritional dynamic in Eucalyptus urophylla x Eucalyptus globulus stand, Eldorado do Sul - RS. For this, was available: a) litter production (leaves, twigs diameter ≤ 1.0 cm, miscellaneous and thick branches diameter > 1.0cm) and nutrients uptake, from 6.5 to 9.5 years-old stand (2007 at 2010); b) leaf litter decomposition and nutrients release by litterbags method (adding 12g of dried leaves in nylon bags), for three years (2007 to 2009); c) aboveground biomass and nutrients amount in the eucalyptus (wood, bark, branches and leaves) and underground (wood and leaves) to ten-year-old stand (June 2010); d) interfere of different intensities of biomass removal (all aboveground biomass removal eucalyptus + underground; eucalyptus removal; wood with bark removal and only wood removal) in relation nutrients stock and; - silvicultural alternative for sustainable forestry management. Litter production was increasing with stand age increasing, showing seasonal behavior with deposition increasing with the air temperature increasing and being mainly composed by leaves fraction that also is main fraction nutrients return through litter. Accumulated litter showed decomposition coefficient of 0.54 with 1.86 years how time average renewal and 1.29 and 5.59 years to disappear 50 and 95% of the litter. Mass loss leaf showed positive correlation with nutrients concentration, indicating that the higher mass loss, higher the nutrients concentration in litter remaining. Litter leaf decay initially showed P, Fe, Mn and Zn immobilization and release of the others, in the second year occurred P release and in the third year occurred Mn and Zn release, with Fe exception. Eucalyptus biomass was allocated predominantly to stem (Wood + bark) with 93.7% and with the largest nutrients stock. Biomass components had different chemical composition, being generally higher in leaves and bark and smaller in wood and branches biomass. With the harvest of wood with the bark all the nutrients removal would suffer more than 45% of the total amount accumulated in aboveground biomass. However, removed just the wood, which has the highest nutrients utilization rate, the nutrients removed percentage, except by Cu and Zn, will be less than 50% and up to 10% in the case of Ca in relation the total biomass contained. Phosphorus and calcium can be the main nutrients became limiting in next rotation productivity, because the potential rotation estimates are close to one, when in the harvest of wood with the bark. Nutrients output through forestry harvest must be take account by companies during the planning of activities. Avoiding productivity decreasing with the next rotations, and also contributing sustainable management, because the nutrients exportation, Ca mainly, is high due to wood with bark harvest.